Cervical Dorsal Rhizotomy Enhances Serotonergic Innervation of Phrenic Motoneurons and Serotonin-Dependent Long-Term Facilitation of Respiratory Motor Output in Rats - Kinkead, Richard (J Neurosci, 1998)
We tested the hypothesis that spinal plasticity elicited by chronic bilateral cervical dorsal rhizotomy (C(3)–C(5); CDR) has functional implications for respiratory motor control. Surgery was performed on rats (CDR or sham-operated) 26 d before phrenic motoneurons were retrogradely labeled with cholera toxin. Rats were killed 2 d later, and their spinal cords were harvested and processed to reveal the cholera toxin-labeled phrenic motoneurons and serotonin-immunoreactive terminals. The number of serotonin-immunoreactive terminals within 5 μm of labeled phrenic motoneuron soma and primary dendrites increased 2.1-fold after CDR versus sham-operation. Time-dependent phrenic motor responses to hypoxia were compared among CDR, sham-operated, and control rats. Anesthetized, paralyzed, vagotomized, and artificially ventilated rats were exposed to three, 5 min episodes of isocapnic hypoxia (Fi(O(2)) = 0.11), separated by 5 min hyperoxic intervals (Fi(O(2)) = 0.5). One hour after hypoxia, a long-lasting, serotonin-dependent enhancement of phrenic motor output (long-term facilitation) was observed in both sham and control rats. After CDR, long-term facilitation was 108 and 163% greater than control and sham responses, respectively. Pretreatment of CDR rats with a 5-HT(2) receptor antagonist (ketanserin tartrate, 2 mg/kg, i.v.) before episodic hypoxia prevented long-term facilitation and revealed a modest (−28 ± 13%; p < 0.05) long-lasting depression of phrenic motor output. The results indicate that CDR: (1) increases serotonergic innervation of the phrenic motor nucleus; and (2) augments serotonin-dependent long-term facilitation of phrenic motor output. These results further suggest a form of plasticity based on changes in the capacity for neuromodulation.